Study to assess the relationship between insertion torque value and implant stability quotient and its influence on timing of functional implant loading - Hasan Sarfaraz; Shefali Johri; P Sucheta; Sripathi Rao (Wolters Kluwer Medknow Publications, 2018)
Purpose: One of the crucial requirements for the success of implants is to achieve good stability. Two well-accepted quantitative methods to assess implant stability, the insertion torque value (ITV), and resonance frequency analysis (RFA) can be a valuable adjunct to radiological and clinical examination. This study was conducted to assess the relationship between ITVs and implant stability quotient (ISQ) and its influence on timing of functional implant loading, as well as to determine the effect of some of the factors on the stability of implants. Materials and Methods: Forty implants were inserted in 37 patients in the posterior mandibular region according to conventional protocol and allowed to heal by placing a healing abutment at the time of placement. For each implant, ITV was measured at the time of the implant placement by manual torque wrench (Nobel Biocare), and the ISQ value was measured by using resonance frequency analyzer (Osstell-ISQ; Integration Diagnostics) at the baseline levels, 3rd week, 7th week, 11th week, and 15th week interval. Results: The correlation between ITV and ISQ was found to be moderately positive and significant (r = 0.399) (P = 0.000). The correlation of ITV value at baseline and ISQ values recorded at the subsequent weeks was also found to be statistically significant at week 3 (r = 0.376) (P = 0.000) and week 7 (r = 0.327) (P = 0.000). Conclusion: It can be concluded from this study that there is a positive and statistically significant correlation between the ITV and ISQ values.